The foundations of Arabic linguistics III : the development of a tradition: continuity and change - Ayoub, Georgine; Versteegh, C. H. M. (Studies in Semitic languages and linguistics, 2018)
All contributions deal with the reception of theories in the Arabic grammatical tradition from the time of Sibawayhi (d. end of the 8th century C.E.) to the later grammarians in the 14th century C.E.